ESMO Consensus Conference on testicular germ cell cancer: diagnosis, treatment and follow-up. (3rd August 2018) - Honecker, F; Aparicio, J; Berney, D; Beyer, J; Bokemeyer, C; Cathomas, R; Clarke, N; Cohn-Cedermark, G; Daugaard, G; Dieckmann, K -P; Fizazi, K; Fosså, S; et al.
Abstract: The European Society for Medical Oncology (ESMO) consensus conference on testicular cancer was held on 3–5 November 2016 in Paris, France. The conference included a multidisciplinary panel of 36 leading experts in the diagnosis and treatment of testicular cancer (34 panel members attended the conference; an additional two panel members [CB and K-PD] participated in all preparatory work and subsequent manuscript development). The aim of the conference was to develop detailed recommendations on topics relating to testicular cancer that are not covered in detail in the current ESMO Clinical Practice Guidelines (CPGs) and where the available level of evidence is insufficient. The main topics identified for discussion related to: (1) diagnostic work-up and patient assessment; (2) stage I disease; (3) stage II-III disease; (4) post-chemotherapy surgery, salvage chemotherapy, salvage and desperation surgery and special topics; and (5) survivorship and follow-up schemes. The experts addressed questions relating to one of the five topics within five working groups. Relevant scientific literature was reviewed in advance. Recommendations were developed by the working groups and then presented to the entire panel. A consensus vote was obtained following whole-panel discussions, and the consensus recommendations were then further developed in post-meeting discussions in written form. This manuscript presents the results of the expert panel discussions, including the consensus recommendations and a summary of evidence supporting each recommendation. All participants approved the final manuscript.